(untitled) (Research, Society and Development, 2021)
Objective: This study aims to learn about self-care and self-perception practices and difficulties related to complications in people with type 2 diabetes mellitus through a Compasso protocol application over the phone. Methods: Cross-sectional study with a quantitative approach that included 222 people with type 2 diabetes. Two instruments were applied: the first composed of sociodemographic information and clinical variables and the second, the Compasso protocol. Results: The difficulties in managing self-care were: physical activity (33.33%) and following the diet plan (32.43%). The possible complications of diabetes that patients believe to have a higher incidence were vision problems (24.32%), cardiovascular complications (22.52%), followed by amputation (19.82%). Most of the participants reported following the diet plan three to four times a week (27.5%), 44.6% did not perform any physical activity at least once a week. 94.6% of the participants reported using the medication every day of the week. However, regarding clinical variables, 58.6% of participants are out of the glycemic goal, with glycated hemoglobin >7%, 44.6% of patients are obese, 61.5% of men and 88.5% of women have a waist circumference above desirable. Conclusions: This study demonstrated that following the diet plan and doing physical activity have been the biggest barriers to self-care of diabetes. Most patients report that problems with vision and cardiovascular complications are the possible consequences of lack of self-care.